Distribution and population size of Cheddar hawkweed Hieracium stenolepiforme (Asteraceae). (2019) - Crouch, Helena J.; McDonnell, Elizabeth J.; Miles, Stephanie; , Timothy C.G. Rich; Crouch, Helena J.; Sell, P. D.; Linton, W. R.
No abstract available